Reliability modeling of multi-version software system incorporating the impact of infected patching. Issue 6 (28th February 2020) - Anand, Adarsh; Kaur, Jasmine; Inoue, Shinji
Abstract : Purpose: The purpose of the present work is to mathematically model the reliability growth of a multi-version software system that is affected by infected patches. Design/methodology/approach: The work presents a mathematical model that studies the reliability change due to the insertion of an infected patch in multi-version software. Various distribution functions have been considered to highlight the varied aspects of the model. Furthermore, weighted criteria approach has been discussed to facilitate the choice of the model. Findings: The model presented here is able to quantify the effect of an infected patch on multi-version software. The model captures the hike in bug content due to an infected patch. Originality/value: Multi-version systems have been studied widely, but the role of an infected patch has not been yet explored. The effect of an infected patch has been quantified by modeling the extra bugs generated in the system. This bug count would prove helpful in further studies for optimal resource allocation and testing effort allocation.